1997
DOI: 10.1557/jmr.1997.0073
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of compositionally modified PbTiO3 thin films prepared by pulsed laser deposition

Abstract: Modified lead titanate of 0.9PbTiO3 −0.1Pb(Mg0.5 W0.5)O3 thin films have been deposited onto Pt-coated Si substrates by pulsed laser deposition. Films were crystallized in situ during deposition or by post-depositional heat treatment (post-annealing). Compositional and structural characterization showed that the phase formation and microstructure of the films were highly sensitive to deposition conditions. Perovskite single phase films were formed in situ at 650 °C, PO2 = 40 Pa as well as by post-annealing amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lee et al have also reported a similar reduction in the tetragonality of films as compared to the bulk target, in compositionally modified lead titanate thin films. 9 The degree of preferred orientation in a film can be represented by a definition proposed by Lotgering 26 which is as …”
Section: Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al have also reported a similar reduction in the tetragonality of films as compared to the bulk target, in compositionally modified lead titanate thin films. 9 The degree of preferred orientation in a film can be represented by a definition proposed by Lotgering 26 which is as …”
Section: Structural Characterizationmentioning
confidence: 99%
“…Perhaps for this reason there are a larger number of reports on doped PbTiO 3 (e.g. La:PbTiO 3 ), [8][9][10][11][12] in which the spontaneous strain is much reduced. The difficulty of the spontaneous strain is avoided by the use of targetless preparation techniques such as solution deposition.…”
Section: Introductionmentioning
confidence: 99%